Understanding clusters of risk factors across different environmental and social contexts for the prediction of injuries among Canadian youth. Issue 5 (May 2016) - Russell, K.; Davison, C.; King, N.; Pike, I.; Pickett, W.
Abstract: Background: Among Canadian youth, injury is the most common reason for presentation to the emergency department. Youth who commonly engage in multiple risk-taking behaviours are at greater risk for injury, but is it unknown if this phenomenon is more pronounced in different contexts. We aimed to study relationships between risk-taking behaviours and injury, and variations in such relationships between different environmental and social contexts, among youth in Canada. Methods: Risk-taking behaviour and injury outcome data were collected from grade 9 to 10 students using the 2009–2010 (Cycle 6) of the Health Behaviour in School-Aged Children Survey ( n = 10, 429). Principal components analysis was used to identify clusters of risk-taking behaviours. Within each identified cluster, the degree of risk-taking was categorized into quartiles from lowest to highest engagement in the behaviours. Risk ratios with 95% confidence intervals were calculated to determine the association between the risk of any injury and the degree of risk-taking behaviour specific to the cluster. Clusters were then examined across home, school, neighbourhood and sport contexts. Results: Four clusters of risk-taking behaviour were identified which were labelled as "gateway substance use", "hard drugs and weapons", "overt risk-taking", and "physical activity". Each cluster was related to injury occurrence in a graded fashion. Clusters of risk behaviour were most strongly associated with injuries sustained in neighbourhood settings, and expectedly, increasing physical activity behaviours were associated with increased risk of sport injuries and injuries occurring at school. Conclusions: This study furthers understanding of clustered risk-taking phenomena that put youth at increasing levels of injury risk. Higher risks for injury and associated gradients were observed in less structured contexts such as neighbourhoods. In contrast, clustered physical activity behaviours were most related to school injury or sport injury and were more likely to be sustained in a supervised context. Understanding the clustered and cumulative nature of risk-behaviours, and how these vary by environmental and social context, helps to explain potential mechanisms of injury as well as modifiable factors that may be important avenues for intervention.